Dynamika Mas Skupionych, Poruszających się po Belce Lezącej na Sprężystym Podłożu - Frąckiewicz, H. (Engineering Transactions, 1965)
The present paper is concerned with the problem of vertical vibration of various sets of concentrated masses moving fast along a beam resting on an elastic foundation (Fig. 1). The equations of motion are derived and the boundary conditions stated. The solutions obtained enable us to estimate the influence of various parameters on the frequencies of natural vibration. The region of harmonic vibration is determined. The paper is illustrated by a number of diagrams in dimensionless coordinates. The results may find application in railway engineering.